BRADYKININ B2 RECEPTOR GENE POLYMORPHISM ANALYSIS IN HYPERTENSIVE PATIENTS AT DR SAIFUL ANWAR HOSPITAL MALANG - Johan Aloysius; Nashi Widodo (University of Brawijaya, 2014)
Hypertension is a major health problem in the world. When blood volume is low, juxtaglomerular cells in the kidneys secrete renin and prorenin activates the blood circulation. Plasma renin converts angiotensinogen released by the liver into angiotensin I, which is then converted to angiotensin II by the enzyme angiotensin converting enzyme (ACE) located in the pulmonary vascular endothelium. Angiotensin II causes blood vessels to constrict, resulting in increased blood pressure. ACEi inhibit the formation of angiotensin I into angiotensin II, and activate Bradykinin (BK), which causes blood vessels to dilate, thereby reducing blood pressure. However, administration of ACEi periodically cause the accumulation of BK in pulmonary vessels that cause inflammation (cough) in some people who suspected mediated by Bradykinin B2 receptor (BK2R) gene. Total of the subjects in this study is 52 subjects, DNA extracted from white blood cells (leukocytes) as much as 200 mL from whole blood by using the QIAamp kit (Qiagen). Gene BK2R in humans amplified by the method of Polymerase Chain Reaction (PCR) method using the following primers F (5-GCAGAGCTCAGCTGGAGGCG-3), and R (5-CCTCCTCGGAGCCCAGAAG-3) and identified by the method of Single Strand Conformation Polymorphism (SSCP). Results of this study shows three different genotypes there are CC, CT, and TT. Subjects with the CC genotype were most susceptible to cough, and subjects with CT genotype were least susceptible. Keywords : ACE inhibitors, B2 Receptor, Cough, SSCP